Large area growth of few-layer In2Te3 films by chemical vapor deposition and its magnetoresistance properties - Shaohui Zhang (Nature Portfolio, 2019)
Abstract In this work we report a facile route to grow large area, uniform, continuous and few-layer α-In2Te3 film via chemical vapor deposition (CVD) methods. The characterizations show the large area of CVD-grown few-layer α-In2Te3. This method guarantees the precise control of thickness down to few layers and large area preparation. The magnetoresistance (MR) properties of few-layer In2Te3 was investigated from 2 to 300 K and its MR stability under long exposure to ambient air was studied for the first time. Few-layer of α-In2Te3 shows a positive MR and the largest transverse MR was observed to about 11% at 2 K and a high stability of MR to long time exposure in air up to 21 weeks.